A fotografia de Pierre Fatumbi Verger: método-Experiência-Afeto - Martins, Daniela Cristiane (2019)
The present study proposes to analyze Pierre Fatumbi Verger's method-experience-affect, from his photographs and, later, by his research in the field of ethnography and anthropology. This method-experience-affect definition was observed after extensive analysis of his personal and visual biography. Verger often argues that he has no preformatted working method and is guided by the “unconscious”. It was this “unconscious” that led us to look more closely at his work and to realize that much of the method-experience-affect is born because of its “tortuous path” and contrary to its Cartesian method. This study was based on the question of portrait, defended by Stella Senra, rostidade, by Gilles Deleuze and Félix Guattari and theory of affection, thought by Baruch de Espinosa.